Comic books and graphic novels for young adults in selected secondary private school libraries in Malabon City with implications towards an encompassing collection development policy - De Castro, A.B. Gideon N.; Cabbab, Johann Frederick A. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2015)
People nowadays can choose assorted types of entertainment through different forms of media. Comic books and graphic novels fall short in terms of educational value compared to reference materials, especially in school libraries. This study therefore seeks to develop an encompassing collection development policy which aims to include comic books and graphic novels in the library collection in consonance to the preference of young adults in Malabon City which are St. Therese of the Child Jesus Academy, Philippine Malabon Cultural Institute, and St. James Academy.
The research instruments involved in this study are survey questionnaires, to know the information needs of the students regarding comics and structured interview to determine the perceptions of the head librarians on the acquisition of comics in their libraries. A total of 161 students were given the survey questionnaire throughout three schools. Three librarians answered the structures interview from each institution. The data on the information needs of the students, because the basis of a library in creating an encompassing collection development policy for comics and graphic novels in their institution.
The data gathered from the survey questionnaire and the structured interview revealed that: (a) 21.8% of the responses show that comedy/humor is the preferred genre by students, (b) 31.0% of the responses prefer comic books as their format, (c) 42.6% of the responses show that leisure is the primary source why students read comics, (d) 96.9% of the students that were surveyed agree to the inclusion of comic books and graphic novels in their libraries, (e) The head librarian or faculty in charge is not familiar with Eisner's Standards for comics in school libraries, (f) School libraries invest more in acquiring reference materials compared to comic books and graphic novels, an (g) Perception of the librarians regarding the inclusion of comics and graphic novels in their holdings vary independently.
This research could convince school administration that comic books and graphic novels as essential as other resource materials within their library. It would also prepare the library staff to introduce these materials as educational tools to the institution's educators and students.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Comic books and teenagers; High-school libraries -- Collection Development; High-school libraries -- Philippines -- Malabon City